2019
DOI: 10.1038/s41598-019-49519-w
|View full text |Cite
|
Sign up to set email alerts
|

Recent decline in vegetative regeneration of bamboo (Yushania alpina), a key food plant for primates in Volcanoes National Park, Rwanda

Abstract: The African montane bamboo Yushania alpina provides both habitat and food for many species in the Albertine Rift region. In Volcanoes National Park (VNP), Rwanda, it is especially important as a key food resource for the Endangered mountain gorilla Gorilla beringei beringei and Endangered golden guenon Cercopithecus mitis kandti. We examined temporal and spatial variation in bamboo shoots regeneration and consumption by primates, monitored between 2013 and 2018 in 82 16-m2 plots located along transects in VNP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…In contrast, in group M which was at higherelevation range, the availability of bamboo shoots was the greatest during the long rainy season (March-May). These findings largely match elevational differences in bamboo regeneration intensities reported in a longterm study in VNP, which revealed that bamboo phenology depends on elevational gradient (van der Hoek et al, 2019). Future studies should investigate the extent of temporal and spatial dietary variation within this population by including more groups and determine how spatial differences in bamboo shoots affect monkey reproduction patterns.…”
Section: Relationship Between Home Range Size Key Food Availability and Consumptionsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, in group M which was at higherelevation range, the availability of bamboo shoots was the greatest during the long rainy season (March-May). These findings largely match elevational differences in bamboo regeneration intensities reported in a longterm study in VNP, which revealed that bamboo phenology depends on elevational gradient (van der Hoek et al, 2019). Future studies should investigate the extent of temporal and spatial dietary variation within this population by including more groups and determine how spatial differences in bamboo shoots affect monkey reproduction patterns.…”
Section: Relationship Between Home Range Size Key Food Availability and Consumptionsupporting
confidence: 83%
“…Like golden monkeys, most large mammals such as the mountain gorillas (Gorilla beringei beringei), African elephant (Loxodonta africana), buffaloes (Syncerus caffer), bush buck (Tragelaphus scriptus), and black fronted duiker (Cephalophus nigrifrons) of the Virunga massif feed on bamboo shoots when available (Plumptre, 1991;Sheil et al, 2012). Given that the gorilla population has been increasing as well as possible increases in other large mammal populations (Granjon et al, 2020;Hickey et al, 2019), we encourage research focusing on interspecific feeding competition in VNP, especially involving bamboo shoots.…”
Section: Determinants Of Ranging Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is quite different from previous research, which stated that the high temperature could stimulate growth and low temperature would inhibit the growth (Banik 2016). Several research proved that elevational variation would affect bamboo growth and the lower elevation provide a greater growth rate on Yushania alpina (Hoek et al 2019) and Chusquea (Clark et al 2015). In addition, according to various species of bamboo, each species has a favorable environmental requirement, such as Chimonobambusa utilis which is optimum on 1.500-2.000 m asl.…”
Section: Resultsmentioning
confidence: 99%
“…Golden monkeys may also be negatively affected by climate change. A study in Volcanoes National Park reported a decline in bamboo regeneration, possibly the result of an overall decrease in rainfall in the Virunga region (van der Hoek et al, 2019). A simulation study focusing on the Albertine Rift predicted a decrease in the extent of habitats preferred by endemic species, including golden monkeys, because of climate change in the coming 6 decades (Ayebare et al, 2018).…”
Section: Discussionmentioning
confidence: 99%